Covert communication method of blockchain network based on transaction construction and forwarding mechanism - Lizhi XIONG; Rong ZHU; Zhangjie FU (Tongxin xuebao)
Aiming at the problems of multiple copies and permanent storage of the transactions containing secret information in the existing storage-based covert communication schemes in blockchain network, as well as the issue of low hidden capacity of the existing time-based schemes, a covert communication method of blockchain network based on transaction construction and forwarding mechanism was proposed.First, an invalid transaction was created by the sender with the help of the transaction construction mechanism, and the secret information was embedded in it, and then the transaction forwarding mechanism was used to send the invalid transaction to the neighbor nodes to form a covert communication channel model, enabling that the transactions containing secret information were spread between nodes and did not exist in the blockchain ledger, so as to achieve the purpose of information concealment and safe transmission.Experimental results show that the transmission capacity of the proposed method is higher than that of the existing schemes, and the single communication time is reduced to 2.5 s.